Compositional Advantage and Strategy: Understanding How Resource-Poor Firms Survive and Thrive - Xin Li (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2016)
In this paper, I first critique the composition-based view of Yadong Luo and John Child for understanding how resource-poor firms survive and thrive. To remedy the deficiencies in their perspective, I then propose a dynamic theory of compositional advantage and strategy. Here, the compositional advantage is redefined as the attractiveness of the composition of the producer's offering in terms of scope and perceived value/price ratio. I identify five ways or basic compositional strategies to improve the value/price ratio. A firm may have an overall compositional strategy that is composed of some or all of the five basic compositional strategies. I argue there are three indispensable key success factors for a composition-based competition, i.e., aspiration (ambition-position asymmetry), attitude (being ALERT), and action (turning asymmetry into advantage). I also discuss the particular relevance of the present theory to understanding Chinese firms. I conclude with managerial implications and suggestions for future research.
hdl:10398/9301
Keywords: 330; Composition; Advantage; Strategy; Value/price ratio; Key success factor; Asymmetry; Produktdifferenzierung; Produktmanagement; Erfolgsfaktor; China